2011
DOI: 10.1146/annurev-neuro-061010-113734
|View full text |Cite
|
Sign up to set email alerts
|

Reward, Addiction, Withdrawal to Nicotine

Abstract: Nicotine is the principle addictive component that drives continued tobacco use despite users’ knowledge of the harmful consequences. The initiation of addiction involves the mesocorticolimbic dopamine system, which contributes to the processing of rewarding sensory stimuli during the overall shaping of successful behaviors. Acting mainly through nicotinic receptors containing the α4 and β2 subunits, often in combination with the α6 subunit, nicotine increases the firing rate and the phasic bursts by midbrain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
316
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(325 citation statements)
references
References 284 publications
(411 reference statements)
8
316
0
1
Order By: Relevance
“…Chronic nicotine is known to up-regulate a4b2* nAChRs in the striatum, thereby increasing dopamine release from dopaminergic terminals (Changeux, 2010). Nicotine's action on these receptors, and a6 receptors, causes a shift in the firing patterns of dopaminergic neurons from tonic, low frequency single-spike firing, to phasic, longer high frequency firing (De Biasi and Dani, 2011). A disproportionate decrease in the tonic firing compared with the phasic signals is also observed in the nucleus accumbens during withdrawal from chronic nicotine (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic nicotine is known to up-regulate a4b2* nAChRs in the striatum, thereby increasing dopamine release from dopaminergic terminals (Changeux, 2010). Nicotine's action on these receptors, and a6 receptors, causes a shift in the firing patterns of dopaminergic neurons from tonic, low frequency single-spike firing, to phasic, longer high frequency firing (De Biasi and Dani, 2011). A disproportionate decrease in the tonic firing compared with the phasic signals is also observed in the nucleus accumbens during withdrawal from chronic nicotine (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The MCL consists predominantly of dopaminergic projections from the midbrain ventral tegmental area to limbic and cortical projection fields in nucleus accumbens (NAc), amygdala, orbitofrontal cortex (OFC), and anterior cingulate cortex (ACC). In the case of tobacco smoking, reinforcing and subsequent addictive effects of nicotine are the result of neuronal acetylcholine receptor (nAChR) activation that modulates 'downstream' events including increased MCL dopamine (DA) release (Tapper et al, 2004;De Biasi and Dani, 2011). The addictive propensity of nicotine is theorized to be due to its quick but short-lived agonistic effect on nAChRs containing α4 and β2 subunits located on the presynaptic membrane of DA neurons (Exley et al, 2011;Tapper et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These mappings are critical in conditions like drug addiction, where our ignorance of how prior beliefs about drugs influence physiological processes related to drugs of abuse presents a profound challenge to the understanding of the mechanism and treatment of addiction (2,3). Although extensive work has shown that addictive drugs act on the mesolimbic dopaminergic (DA) pathway (2,4), it has become clear that these purely biochemical explanations are not sufficient to account for the huge heterogeneity among drug-dependent individuals and the low success rate of quitting and remaining drug-free (2,5) and that cognitive factors such as beliefs and expectations have a profound impact on drug-related neurobiological effects (6,7).…”
mentioning
confidence: 99%
“…Striatal DA levels are also modulated by prediction errors about alcohol (21). It is thus reasonable to suspect that beliefs about nicotine could modulate the key neural signals involved in nicotine addiction (4,31). These same neural signals that guide Significance Nicotine is the primary addictive substance in tobacco, which stimulates neural pathways mediating reward processing.…”
mentioning
confidence: 99%
See 1 more Smart Citation